UNDERSTANDING AUDIT METHODS TO ASSIST PLANNING ON PROGRAM EVALUATION: SHARING GAO'S EXPERIENCE ON NATIONAL HEALTH SECURITY PROGRAM - Adnyana, I Gede Sudi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2017)
BPK has a mandate to conduct a performance audit for examining whether government agencies have implemented their critical programs in the possible aspects of efficiency, effectiveness, or economy. Nevertheless, the current audit methods for those government programs designed at the planning stages by the audit teams have not been fully emphasized on one or a combination of four main types of evaluation, such as process and/or implementation evaluation; outcome evaluation; impact evaluation; and cost-benefit and cost-effectiveness analyses. They can be identified by using measures of program performance, along with other information, to study the benefits of a program or how to improve it. The program chosen is the NHS program, evaluated by using GAO's experience which was empirically implemented and observed by the author during the fellowship program in the Agency. This study discusses the evaluation of FOD evaluation and a general guide to address researchable questions derived from NHS program stage evaluation, analysis of researchable question types, and to consider some challenges at designing evaluations. Further, BPK could improve the methods and design of its performance audit plan as regards program evaluation by considering such variables that have been applied in their best practices.